Penyuluhan Perencanaan Rumah Tahan Gempa Kepada Siswa SMK Negeri 1 Ujung Batu - Ahmad hamidi; Haniza, Sjelly; Jusi, Ulfa; Maizir, Harnedi; Yasri, Desi; Zuhro (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2022)
A building, especially a building and a residence, is an absolute primary physical facility for modern humans whose function is to provide a place for them to live and work. As time goes by, the need for housing has become one of the main needs in carrying out activities, so to support the movement of human activities, a building that meets the structural and comfort requirements is needed. The structural requirement in question is a strong building to withstand earthquake loads because in general Indonesia is on the ring of fire line from the composition of the area with a high enough earthquake risk so for planning the building must meet the requirements of a strong structure. The design of earthquake-resistant buildings is not only for tall buildings but also for simple buildings such as residential houses so that if an earthquake occurs, the building will still stand strong and the people who live in the house are still in a safe condition.